2006
DOI: 10.1111/j.1750-3841.2006.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination Efficacy of Combined Chlorine Dioxide with Ultrasonication on Apples and Lettuce

Abstract: The bacterial reduction of Salmonella and Escherichia coli O157:H7‐inoculated apples and lettuce by ClO2 at 0, 5, 10, 20, and 40 ppm with and without 170‐kHz ultrasonic treatments for 3, 6, and 10 min, respectively, have been studied. The treatments of ClO2 at 20 and 40 ppm for 3, 6, and 10 min or at 5 and 10 ppm for 6 and 10 min with 170‐kHz ultrasonication caused 3.115 to 4.253 log reductions in Salmonella and 2.235 to 3.865 log reduction in E. coli O157:H7 on inoculated apples. Using combined ClO2 and ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(48 citation statements)
references
References 14 publications
3
44
0
1
Order By: Relevance
“…3. Reductions resulting from SAEW treatment were always more than 1 log CFU/mL and significantly (p<0.05) differed from the control (no treatment), regardless of the treatment time, in agreement with previous reports that SAEW is an effective method for food decontamination (7,8,19,24), but different from previous studies suggesting that 3 min was the best treatment time for SAEW treatments (18,19,25,26). In this study, 1 min was used as the treatment time since 3 and 5 min treatment times resulted in similar degrees of microbial reduction, perhaps due to higher amounts of organic materials (protein/lipid) in kashk, compared with all the foods treated using SAEW in previous reports (1).…”
Section: Resultssupporting
confidence: 76%
“…3. Reductions resulting from SAEW treatment were always more than 1 log CFU/mL and significantly (p<0.05) differed from the control (no treatment), regardless of the treatment time, in agreement with previous reports that SAEW is an effective method for food decontamination (7,8,19,24), but different from previous studies suggesting that 3 min was the best treatment time for SAEW treatments (18,19,25,26). In this study, 1 min was used as the treatment time since 3 and 5 min treatment times resulted in similar degrees of microbial reduction, perhaps due to higher amounts of organic materials (protein/lipid) in kashk, compared with all the foods treated using SAEW in previous reports (1).…”
Section: Resultssupporting
confidence: 76%
“…Huang et al (2006) observed that 170 kHz ultrasound removed more efficiency Salmonella than E. coli O157:H7 from apples surface. These authors also observed that the combination of chemical treatments and ultrasounds resulted in a greater reduction of the contaminant population on fruits and vegetables.…”
Section: Resultsmentioning
confidence: 95%
“…Soli et al (2010) reported the efficacy of combinations of weakly acidic hypochlorous water, pretreatment with sucrose fatty acid ester, micro-bubbling, and mild heating for sanitizing lettuce, which reduced viable counts by 3 _ 4 log. Huang et al (2006) described the efficacy of chlorinated water combined with ultra-sonication against E. coli O157:H7 in strawberries and broccoli. However, few of these studies have examined the efficacy of combining chlorination with physical treatments.…”
Section: Introductionmentioning
confidence: 99%